2007
DOI: 10.1029/2006jb004667
|View full text |Cite
|
Sign up to set email alerts
|

Postseismic quasi‐static fault slip due to pore pressure change on a bimaterial interface

Abstract: [1] We theoretically study the mechanism of afterslip, generally observed after the occurrence of large shallow earthquakes, taking account of poroelastic effects including fluid flow. A two-dimensional in-plane shear fault is assumed on a bimaterial interface that separates mechanically different poroelastic media. We first derive analytical expressions for the stress tensor components and fluid pressure as integrals of fault slip; the rigidity and diffusivity of the two media separated by the fault are assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 41 publications
(64 reference statements)
5
31
0
Order By: Relevance
“…When the two mechanisms produce competing changes, the bimaterial effects associated with the large‐scale elastic contrast are likely to be larger for rupture velocities near the generalized Rayleigh wave speed. Yamashita (2007) found with quasi‐static calculations that a contrast of elastic and diffusivity properties across a fault lead to strongly asymmetric distribution of afterslip. It would be interesting to examine the interaction between large‐scale bimaterial contrast and small‐scale fluid‐related effects in simulations that account also for off‐fault damage, which is expected to modify considerably the permeability and diffusivity properties.…”
Section: Discussionmentioning
confidence: 88%
“…When the two mechanisms produce competing changes, the bimaterial effects associated with the large‐scale elastic contrast are likely to be larger for rupture velocities near the generalized Rayleigh wave speed. Yamashita (2007) found with quasi‐static calculations that a contrast of elastic and diffusivity properties across a fault lead to strongly asymmetric distribution of afterslip. It would be interesting to examine the interaction between large‐scale bimaterial contrast and small‐scale fluid‐related effects in simulations that account also for off‐fault damage, which is expected to modify considerably the permeability and diffusivity properties.…”
Section: Discussionmentioning
confidence: 88%
“…Detailed parameter space studies indicate that ruptures on a bimaterial interface tend to evolve during propagation from initial symmetric cracks with relatively low mechanical efficiency to slip pulses with preferred propagation direction and high mechanical efficiency [e.g., Shi and Ben‐Zion , 2006; Brietzke et al , 2007; Dalguer and Day , 2007; Ampuero and Ben‐Zion , 2008; G. B. Brietzke et al, Importance of bimaterial interfaces for earthquake dynamics and strong ground motion, submitted to Geophysical Journal International , 2008]. Local permeability contrast across the fault can also produce asymmetric rupture as well as asymmetry of aseismic slip [ Rudnicki and Rice , 2006; Yamashita , 2007]. The progressive development of bimaterial interfaces in fault zone structures is expected to change over geological time the mode of earthquake ruptures on the fault, the energy partition during the faulting process, the ability of the fault to localize future earthquake ruptures, and a variety of related dynamic and evolutionary phenomena [ Ben‐Zion and Andrews , 1998; Ben‐Zion , 2001].…”
Section: Scale Invariance Versus Characteristic Scalesmentioning
confidence: 99%
“…In contrast to his treatment, our concern here is about the effect of contrast in the hydraulic diffusivity on the generation of afterslip. Hence, our present article and the paper of Yamashita [2007] (hereinafter referred to as Paper I) form a complementary pair.…”
Section: Introductionmentioning
confidence: 97%
“… Yamashita [2007] theoretically and numerically studied the generation mechanism of afterslip taking account of spatiotemporal change of pore fluid pressure and bimaterial fault structure. He showed that quasi‐static fault tip extension is triggered by the sudden introduction of fault slip on the assumption of a fault on an interface that separates two poroelastic media with different values of drained and undrained Poisson's ratios and the Biot‐Willis coefficient.…”
Section: Introductionmentioning
confidence: 99%